Irony Expressed by Adjectives and Verbs in English Literature - Mavlonova Ugiloy Khamdamovna (International Journal on Integrated Education, 2022)
In the article, the translation of “The Master and Margarita” by Russian writer Mikhail Bulgakov is studied by several translators with an in-depth analysis of examples of irony expressed by adjectives and verbs.